Measuring coverage of nutrition counselling interventions: Leveraging available data and program experiences - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Thirty state-wise Data Notes were prepared that describe the coverage of a set of key nutrition and health interventions in each individual state. http://poshan.ifpri.info/category/publications/data-notes/